Prediction of Financial Distress in Companies on The Indonesian Stock Exchange - Sinarti, Sinarti; Nurfitriadi, Ayu (Politeknik Negeri Batam, 2024)
This research aims to determine the potential profit and cash flow by using the Altman Z-Score prediction model in predicting financial distress in manufacturing companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, 98 manufacturing companies were obtained that were listed on the Indonesia Stock Exchange in the 2015-2019 period. The results of research on the sample show that profits and cash flow using the Altman Z-Score prediction model can predict financial distress in manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2019 period.